Ischemic stroke in young women with a patent foramen ovale: cases reports - E. E. Matvienko; M. D. Matvienko (Российский кардиологический журнал, 2025)
Introduction. Causal relationship between minor congenital heart defects and neurological pathology remains a relevant and debatable issue.Brief description. Two cases of ischemic stroke of different locations associated with patent foramen ovale (PFO) are presented in patients aged 20 and 32 years without other risk factors.Conclusion. In both cases of cryptogenic stroke, an examination for PFO by transesophageal echocardiography and bilateral cerebral microemboli monitoring were performed. Diagnosis of a right-to-left shunt in the first case was difficult and required a repeat bubble and transesophageal echocardiography with contrast enhancement and the Valsalva maneuver. Confirmation of functioning PFO allowed us to clarify the pathogenetic variant of stroke, determine the tactics of treatment and secondary prevention measures.